187 The Inflammatory Phenotype of the Tilrr Knockout Mouse - Mechanisms Undelying Reduced Responses to Vascular Injury. (31st May 2014) - Murphy, Emer; Samokhin, Andriy; Francis, Sheila; Bowskill, Susannah; Qwarnstrom, Eva
Abstract : Background: TILRR, an IL-1R1 co-receptor, is a strong amplifier of IL-1-induced inflammatory and anti-apoptotic signals controlled by NF-κB. 1 Our recent work has demonstrated that TILRR is highly expressed at areas of inflammation such the atherosclerotic plaque, and that inhibiting TILRR function, using a blocking peptide antibody, reduces plaque development in a mouse model of atherosclerosis (Samokhin et al, unpublished). This study focuses on characterisation of the inflammatory phenotype of a TILRR knock-out mouse, which was created to further assess the role of TILRR in vascular disease. Methods and results: Wild-type and TILRR null mice were injected intraperitoneally with lipopolysaccharide (LPS) or PBS control. Animals were sacrificed at 3 or 12 h and cells from blood and spleen analysed by FACS. Protein and RNA levels were determined by western blotting, qPCR and microarray. Our results demonstrate a 50% decrease in neutrophil levels in the TILRR KO mice compared to wild type, following LPS injection. In addition, FACS analysis revealed a reduction in inflammatory monocytes, with a corresponding increase in the non-inflammatory phenotype. Further, TILRR knockout caused on average a 50% reduction in IL-1 receptor levels, and resulted in a decrease in ligand-induced activation of NF-κB and in release of inflammatory mediators, such as IL-6 and IL-8. Ongoing microarray analysis will determine the impact of these changes on overall gene activation profiles in TILRR knockouts. Based on initial studies using TILRR siRNA, the absence of TILRR expression is expected have pronounced effects on multiple genes relevant to control of vascular inflammation. Conclusion: The results are consistent with a central role for TILRR in regulating inflammatory processes in vivo . Our data show that TILRR deficient mice exhibit reduced responses to systemic inflammation, and show that these are induced at the level of receptor function and signal transduction. The findings agree with work carried out in parallel, focusing on the role of TILRR in cardiovascular injury and disease. Supported by the BHF and BBSRC. References: Zhang X, Shephard F, Kim HB, Palmer IR, Mcharg S, Fowler GJ, O'Neill LA, Kiss-Toth E, Qwarnstrom EE. TILRR, a novel IL-1RI co-receptor, potentiates MyD88 recruitment to control Ras-dependent amplification of NF-kappaB. J Biol Chem 2010;285:7222–32 Zhang X, Montagut Pino G, Shephard F, Kiss-Toth E, Qwarnstrom EE. Distinct control of MYD88-dependent and AKT-regulated responses by the IL-1RI co-receptor, TILRR. J Biol Chem 2012;287:12348–12352